A method for preparing a high catalytic activity composite material and its application in lithium-sulfur batteries

By preparing highly catalytically active composite materials, the problems of poor sulfur conductivity and slow reaction kinetics in lithium-sulfur batteries are solved, which significantly improves the discharge capacity, cycle stability and rate performance of lithium-sulfur batteries, and achieves more efficient electrochemical reactions .

CN117038901BActive Publication Date: 2024-12-24ZHENGZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311026122.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2024-12-24
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

Lithium sulfur batteries have poor conductivity, slow electron transfer speed, slow electrode reaction kinetics, resulting in low discharge capacity and poor circulation performance. The reaction process involves multiple "solid-liquid-solid" conversion. This leads to poor battery performance, limiting its commercial application.

Method used

The preparation method of high catalytically active composite materials is adopted to prepare zinc-based metal organic framework materials, uniformly disperse molybdenum source, and carbonization to obtain MoC nanoquantum dots. Then, metal salts are adsorbed by solution impregnation, and single-atom-loaded X@MoC is prepared by high-temperature carbonization. /C composite material used to improve the conversion reaction kinetics and electrochemical properties of lithium-sulfur batteries.

Benefits of technology

It significantly improves the discharge specific capacity, cycling performance and rate performance of lithium-sulfur batteries, enhances the electrochemical reaction kinetics, reduces the shuttle and battery polarization of polysulfides, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117038901B_ABST
    Figure CN117038901B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a composite material with high catalytic activity and its application in a lithium-sulfur battery, comprising the following steps: preparing a zinc-based metal organic framework material Zn-MOF; uniformly dispersing a molybdenum source on the zinc-based metal organic framework material; carbonizing at high temperature in an inert atmosphere to obtain a carbon material MoC / C in which MoC nano-quantum dots are uniformly dispersed; adsorbing a metal salt on the MoC / C material by a solution impregnation method; and carbonizing at high temperature in an inert atmosphere to obtain a single-atom-loaded X@MoC / C composite material. The composite material has a rich pore structure and abundant catalytic active sites. It is applied to the positive electrode and diaphragm of a lithium-sulfur battery, which not only improves the transmission of electrons and ions, but also can effectively adsorb polysulfides. The high catalytic active sites accelerate the kinetics of the redox reaction, promote the reaction, and play a role in limiting the shuttle effect of polysulfides, significantly improving the discharge capacity, rate performance and cycle stability of the lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy materials, and in particular to a method for preparing a composite material with high catalytic activity and application of the composite material in a lithium-sulfur battery. Background Art

[0002] With the popularization of electronic products and electric vehicles, as well as the rapid development of energy storage power stations and smart grids, people have put forward higher requirements on the energy density and service life of batteries. The performance of existing lithium-ion batteries can no longer meet the requirements, so a new battery system must be developed. Lithium-sulfur batteries have a high theoretical specific capacity (1675 mAh / g) and a high energy density (2500 Wh / kg), which are several times the energy density of current commercial lithium-ion batteries. In addition, sulfur has the advantages of abundant resources, low cost, and environmental friendliness. It is considered to be one of the most promising battery technologies for the next generation. However, lithium-sulfur batteries also face many problems: the positive electrode active material sulfur and the reaction product Li 2 S has poor conductivity, slow electron transfer, and slow electrode reaction kinetics; the intermediate product in the charge and discharge process is soluble polysulfide, which triggers the shuttle effect; and the reaction process involves a multi-step "solid-liquid-solid" conversion process, which not only brings about the problem of large electrode volume expansion, but also requires overcoming higher reaction energy barriers. These problems will lead to low discharge capacity and poor cycle performance of lithium-sulfur batteries, which restrict the development of lithium-sulfur batteries and limit their commercial application.

[0003] Since the inherent properties of sulfur and polysulfides are the root causes of the above problems, multifunctional highly conductive porous materials are usually designed and developed to be combined with sulfur to improve the electrochemical performance of the sulfur cathode. The conductivity of the sulfur cathode is improved by improving the conductivity of the material, and the utilization rate of sulfur is improved; the porous structure plays a physical confinement role on polysulfides, which can alleviate the volume expansion of sulfur and limit the dissolution of polysulfides; by increasing polar sites through nitrogen doping, introducing defects, etc., it is beneficial to the adsorption of polysulfides by the carrier material and more effectively inhibit the diffusion of polysulfides. In addition, in recent years, materials with electrocatalytic activity have been used in lithium-sulfur batteries. The introduction of catalytic materials can enhance the redox kinetics of polysulfides and promote the electrochemical reaction of electrodes. As one of the key components of lithium-sulfur batteries, the diaphragm also plays a vital role in the performance of lithium-sulfur batteries. The current commercial diaphragms are prone to polysulfide shuttle due to their porous and large pores. Therefore, it is also an effective method to accelerate the polysulfide conversion process by coating the diaphragm surface with materials that have adsorption and catalytic conversion effects on polysulfides. However, although catalytic materials can improve the electrochemical performance of lithium-sulfur batteries to a certain extent, a single catalytic material still has great limitations for the multi-step reactions of lithium-sulfur batteries. Therefore, there is a lack of effective composite materials with multiple catalytic active centers to meet the further development of lithium-sulfur batteries. Therefore, the development of highly catalytic and multi-active site composite materials for application in lithium-sulfur batteries is of great significance.

[0004] The purpose of the present invention is to design a multifunctional high-activity catalytic material with physical confinement, chemical adsorption and catalytic conversion effects on lithium polysulfide, and to apply it in the field of lithium-sulfur batteries to improve the discharge capacity, cycle stability and rate performance of lithium-sulfur batteries. Summary of the invention

[0005] In order to solve the problems existing in the above-mentioned lithium-sulfur batteries, the present invention provides a method for preparing a high catalytic activity composite material and its application in a lithium-sulfur battery. The composite material is applied in a lithium-sulfur battery, and the porous structure can physically confine and chemically adsorb polysulfides. A large number of high catalytic activity sites improve the conversion reaction kinetics of the lithium-sulfur battery, which can significantly improve the discharge specific capacity, cycle performance and rate performance of the lithium-sulfur battery.

[0006] The present invention solves the technical problem by adopting the following technical solutions:

[0007] A method for preparing a composite material with high catalytic activity comprises the following steps:

[0008] (1) Preparation of zinc-based metal organic framework material Zn-MOF;

[0009] (2) uniformly dispersing the molybdenum source on the zinc-based metal organic framework material;

[0010] (3) carbonizing the material obtained in step (2) at high temperature under an inert atmosphere to obtain a carbon material MoC / C in which MoC nano-quantum dots are uniformly dispersed;

[0011] (4) Adsorbing metal X salt onto MoC / C material by solution impregnation method;

[0012] (5) The material obtained in step (4) is carbonized at high temperature under an inert gas atmosphere to obtain a single-atom-loaded X@MoC / C composite material with high catalytic activity.

[0013] Furthermore, the metal organic framework material in step (1) is a zinc-based metal organic framework material composed of a combination of zinc metal ions and organic ligands, such as ZIF-7, ZIF-8, ZIF-62, ZIF-90, MOF-5, MOF-74 (Zn), MOF-177, etc. The preparation method of the zinc-based metal organic framework material can be a conventional preparation method in the art, such as hydrothermal / solvothermal synthesis, ultrasonic method, microwave heating method, electrochemical method and mechanochemical synthesis method, etc.

[0014] Preferably, the zinc-based metal organic framework material prepared in step (1) has a particle size of 50 nm to 5 μm, has a rich pore structure such as micropores and mesopores, and a specific surface area greater than 300 m 2 / g.

[0015] Preferably, the organic ligand of the zinc-based metal organic framework material prepared in step (1) contains nitrogen.

[0016] The molybdenum source in step (2) is molybdenum hexacarbonyl (Mo(CO) 6 ), the mixing method is physical or chemical, and the mass ratio of molybdenum hexacarbonyl to Zn-MOF is 2:100~50:100.

[0017] Preferably, the mass ratio of molybdenum hexacarbonyl to Zn-MOF is in the range of 10:100 to 30:100.

[0018] Furthermore, in step (3), the inert gas is nitrogen or argon, the high-temperature carbonization temperature is 900-1100°C, and the time is 1-4 hours. The zinc in the Zn-MOF evaporates along with the air flow at high temperature to obtain a carbon material MoC / C in which MoC nano-quantum dots are uniformly dispersed.

[0019] In the step (4), the solution impregnation method is to uniformly disperse the MoC / C material in the X metal salt solution, and after magnetic stirring and impregnation for 6 to 18 hours, collect the precipitate by centrifugation or suction filtration, wash it with deionized water and ethanol, and place it in a vacuum oven at 60°C for 4 to 12 hours to prepare the metal salt adsorbed MoC / C material, wherein the metal element X is one or more transition metal elements, the X metal salt includes acetate, nitrate, chlorate, chloride, etc. of the X metal, the concentration of metal ions in the metal salt solution is 0.1 to 10 mg / mL, and the solution can be deionized water, ethanol, etc.

[0020] Preferably, the transition metal element is nickel, cobalt, iron, manganese, chromium, etc.

[0021] Preferably, the mass ratio of the MoC / C material to the metal ions is 100:0.5 to 100:1.5.

[0022] The inert gas in step 5 is nitrogen or argon, the high-temperature carbonization temperature is 500-800°C, and the time is 1-2 hours to obtain a single-atom-loaded X@MoC / C composite material.

[0023] Preferably, the carbonization temperature is 700-800° C., and the carbonization time is 1 hour.

[0024] The present invention also provides a single-atom-loaded X@MoC / C composite material with high catalytic activity prepared by the preparation method. In the composite material, carbon is used as a carrier material and has a rich pore structure, and the mass fraction of carbon ranges from 50% to 99%; MoC is distributed on the carbon carrier in the form of nano-quantum dots, and the average size of MoC is less than 5 nm, and the mass fraction ranges from 1% to 50%; the metal element X exists in the form of a single atom, and the mass fraction ranges from 0.1% to 2%.

[0025] Preferably, the specific surface area of ​​the composite material is greater than 500 m 2 / g, the prepared zinc-based metal organic framework material has a particle size of 100 nm~1 μm, has a rich pore structure such as micropores and mesopores, and a pore volume of more than 0.5 cm 3 / g.

[0026] Preferably, the mass fraction of MoC is 10% to 30%, and the mass fraction of single atoms is 0.5% to 2%.

[0027] The present invention also provides a lithium-sulfur battery, wherein the positive electrode or the separator of the lithium-sulfur battery contains the single-atom-loaded X@MoC / C composite material with high catalytic activity.

[0028] The present invention also provides an application of a high catalytic activity composite material in a lithium-sulfur battery, wherein the X@MoC / C composite material is used as a positive electrode sulfur-carrying material or a modified commercial battery separator, or as both a positive electrode sulfur-carrying material and a modified commercial battery separator.

[0029] The above-mentioned single-atom-loaded X@MoC / C composite material with high catalytic activity is used as the positive electrode sulfur-carrying material of the lithium-sulfur battery. The specific steps are as follows:

[0030] (a) After the sublimated sulfur and the X@MoC / C composite material are uniformly mixed in a certain mass ratio, the sulfur powder and the high catalytic active carbon material are mixed by melt filling sulfur under vacuum or inert gas protection atmosphere to obtain a sulfur / carbon composite positive electrode material. The melting heating temperature is 155 °C and the temperature is kept for 12 to 24 hours. The mass ratio of X@MoC / C material in the sulfur / carbon composite positive electrode material is 5% to 50%.

[0031] Preferably, vacuum sulfur loading is used, and the mass proportion of X@MoC / C material in the obtained composite positive electrode material is 10%~40%.

[0032] (b) The sulfur-carbon composite positive electrode material, conductive agent and binder obtained in step (a) are mixed in a certain proportion, using nitrogen methyl pyrrolidone (NMP) as a solvent, and the slurry is evenly mixed to form a slurry, which is then coated on an aluminum foil current collector and vacuum dried to prepare a lithium-sulfur battery positive electrode sheet.

[0033] Preferably, in the certain proportion, the proportion of sulfur-carbon composite positive electrode material is 80-90%, the proportion of conductive agent is 5-10%, and the proportion of binder is 5-10%.

[0034] The conductive agent is one or more of conductive carbon black, conductive graphite, carbon nanotubes, and graphene, and the binder is polyvinylidene fluoride.

[0035] Preferably, the homogenization mixing method adopts a ball milling method, the ball milling time is 1 to 2 hours, and the sulfur loading of the positive electrode of the lithium-sulfur battery is 0.5 to 5 mg / cm 2 .

[0036] (c) Assembling the positive electrode sheet obtained in step (b) and the lithium negative electrode, the separator, the electrolyte and the shell to obtain a lithium-sulfur battery.

[0037] The diaphragm is a microporous polyolefin diaphragm, a ceramic diaphragm or a non-woven fabric diaphragm, etc. Preferably, the polyolefin diaphragm is composed of one or more layers of polyethylene (PE) or polypropylene (PP).

[0038] The commercial battery separator is modified by using the above-mentioned single-atom-loaded X@MoC / C composite material with high catalytic activity. The specific steps are as follows:

[0039] (a) The X@MoC / C composite material is mixed with a conductive agent and a binder in a certain proportion, and nitrogen methyl pyrrolidone is used as a solvent. The mixture is evenly mixed to form a slurry, which is then coated on one side of a commercial diaphragm by scraping, filtering, spraying, etc., and then vacuum dried to obtain a modified diaphragm, wherein the commercial diaphragm is a microporous polyolefin diaphragm, a ceramic diaphragm or a non-woven fabric diaphragm.

[0040] Preferably, the certain proportion is 70-90% of the X@MoC / C composite material, 10-20% of the conductive agent, and 10-20% of the binder, which are evenly mixed and then coated on the surface of the diaphragm.

[0041] Preferably, the membrane surface modification material loading is 0.1-0.3 mg / cm 2 .

[0042] (b) Assembling the modified separator obtained in step (a) with the positive electrode, the negative electrode, the electrolyte and the outer shell to obtain a lithium-sulfur battery.

[0043] Preferably, the positive electrode adopts a single-atom-loaded X@MoC / C composite material with high catalytic activity as a pole piece prepared by the positive electrode sulfur-carrying material of the lithium-sulfur battery, and the electrolyte is composed of a lithium-containing electrolyte, a non-aqueous organic solvent and lithium nitrate. The electrolyte is lithium bistrifluoromethanesulfonyl imide (LiTFSI) with a concentration of 1 mol / L, and the non-aqueous organic solvent is a mixed solvent of dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1, and the mass ratio of the added lithium nitrate is 1%.

[0044] Beneficial effects of the present invention:

[0045] The present invention provides a method for preparing a composite material with high catalytic activity. A porous carbon material loaded with MoC nano-quantum dots is prepared by a clever one-step method, and then a metal salt is adsorbed by a solution impregnation method and then carbonized at high temperature in an inert gas environment to obtain a single-atom-loaded X@MoC / C composite material with high catalytic activity and multiple active sites.

[0046] The single-atom-loaded X@MoC / C composite material prepared by the present invention has a large pore volume and a rich pore structure. As a carrier of the positive electrode material of a lithium-sulfur battery, it plays a role in physical confinement and chemical adsorption of polysulfides. At the same time, the embedding of single atoms and MoC nano-quantum dot active sites increases the electron transmission capacity and the number of active sites of the composite material. It has high active catalytic performance. As a sulfur positive electrode carrier of a lithium-sulfur battery or a modified diaphragm, it can well improve the reaction kinetics of the lithium-sulfur battery, accelerate electron transmission during the electrochemical reaction, reduce the shuttling of polysulfides, and reduce battery polarization. The experimental results show that the single-atom-loaded X@MoC / C composite material is used in lithium-sulfur batteries, which significantly improves the discharge capacity, rate performance and cycle stability of lithium-sulfur batteries. The preparation method of the present invention has mild reaction conditions, simple process, environmental friendliness, and is easy to prepare in batches, which is of great significance for the further commercialization of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0048] Figure 1 This is an X-ray diffraction (XRD) diagram of the Ni@MoC / C material prepared in an embodiment of the present invention;

[0049] Figure 2 This is a scanning electron microscope (SEM) image of the Ni@MoC / C material prepared in an embodiment of the present invention;

[0050] Figure 3 Transmission electron microscope image (TEM) and elemental surface scanning image (mapping) of the Ni@MoC / C material prepared in the embodiment of the present invention;

[0051] Figure 4 Nitrogen isothermal adsorption-desorption curve and pore size distribution diagram (BET) of the Ni@MoC / C material prepared in the embodiment of the present invention;

[0052] Figure 5 This is the full X-ray photoelectron spectroscopy (XPS) spectrum of the Ni@MoC / C material prepared in the embodiment of the present invention;

[0053] Figure 6 This is an X-ray absorption fine structure spectrum (XAFS) diagram of the Ni@MoC / C material prepared in an embodiment of the present invention;

[0054] Figure 7A cyclic voltammetry (CV) curve of the material prepared in the embodiment of the present invention applied in a lithium-sulfur battery;

[0055] Figure 8 A cyclic voltammetry curve (CV) of the material prepared in the comparative example of the present invention applied in a lithium-sulfur battery;

[0056] Fig. 9 For the embodiment of the present invention ( Figure 7 ) and the comparative example ( Figure 8 )’s cyclic voltammetry curve reduction and oxidation peak voltage comparison diagram;

[0057] Fig.10 The discharge performance diagram of the material prepared in the embodiment of the present invention and the material prepared in the comparative example when used in a lithium-sulfur battery at different current densities (0.2 C, 0.5 C, 1 C, 2 C);

[0058] Fig.11 Cyclic performance diagram of the material prepared in the embodiment of the present invention and the material prepared in the comparative example when used in a lithium-sulfur battery at a current density of 0.5 C;

[0059] Fig.12 Cycling performance diagram of the material prepared in the embodiment of the present invention and the material prepared in the comparative example when used in a lithium-sulfur battery at a current density of 1 C;

[0060] Among them, the XRD graph obtained has a diffraction angle (2θ) on the horizontal axis and a diffraction peak intensity (Intensity) on the vertical axis; the nitrogen isothermal adsorption-desorption curve obtained has a relative pressure on the horizontal axis and a nitrogen adsorption volume on the vertical axis; the XPS graph obtained has an electron binding energy on the horizontal axis and an electron intensity on the vertical axis; the X-ray absorption fine structure spectrum (XAFS) graph obtained has an absorption energy on the horizontal axis and an absorption intensity on the vertical axis; the cyclic voltammetry graph obtained has a voltage on the horizontal axis and a current on the vertical axis; the reduction and oxidation peak voltage comparison graph of the cyclic voltammetry curve obtained has a reduction peak 1 (Cathodic Ⅰ), a reduction peak 2 (Cathodic Ⅱ) and an oxidation peak (Anodic) corresponding to the cyclic voltammetry curve on the horizontal axis and a voltage on the vertical axis; the cycle performance graph and rate performance graph obtained have a cycle number on the horizontal axis and a specific capacity on the vertical axis. capacity). DETAILED DESCRIPTION

[0061] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Example 1

[0063] Preparation of Ni@MoC / C composite materials containing single atom loading and its application as positive electrode sulfur-carrying materials in lithium-sulfur batteries.

[0064] The preparation method of the Ni@MoC / C composite material containing single atom loading in this embodiment is as follows:

[0065] 1. Preparation of zinc-based metal organic framework material ZIF-8

[0066] First, 9 g of zinc nitrate (Zn(NO 3 ) 2 6H 2 O) was added to 450 mL of methanol (CH 3 OH) solution, and then 9.24 g of 2-methylimidazole (C 4 H 6 N 2 ) was added to another 450 mL of methanol solution. After the two solutions were completely dissolved, the 2-methylimidazole solution was added to the zinc nitrate solution, ultrasonicated for 10 minutes, and magnetically stirred at room temperature for 24 hours. The precipitate was collected by centrifugation at a speed of 6000 r / min and a centrifugal time of 2 min. Finally, it was washed with methanol solution for more than three times and dried in a vacuum oven at 60°C for 6 hours to obtain ZIF-8 nanoparticles.

[0067] 2. Disperse the molybdenum source evenly on the zinc-based metal organic framework material

[0068] Weigh 40 mg of molybdenum hexacarbonyl (Mo(CO) 6 ) material, placed in a 3 mL open glass bottle; weigh 0.2 g of ZIF-8 powder and place it in a 20 mL glass bottle. Then, place the 3 mL open glass bottle in the 20 mL glass bottle, tighten the cap of the 20 mL glass bottle, and then place the 20 mL glass bottle in a forced air oven, and set the oven to 85 ° C for 12 hours. After the 20 mL glass bottle naturally cools to room temperature, open the lid and take out the material to obtain ZIF-8 powder adsorbing molybdenum hexacarbonyl.

[0069] 3. Preparation of carbon material MoC / C with uniform dispersion of MoC nano-quantum dots

[0070] The ZIF-8 powder adsorbing molybdenum hexacarbonyl obtained in step 2 is placed in a corundum boat, and then the corundum boat is placed in a tubular furnace, and the temperature is increased to 910°C at a rate of 5°C / min under an argon atmosphere. After being kept at 910°C for 3 hours, it is naturally cooled to room temperature with the furnace. During the high-temperature carbonization process, the zinc in the ZIF-8 evaporates with the air flow at high temperature, and the molybdenum hexacarbonyl is converted into MoC. The collected black powder material is the carbon material MoC / C in which MoC nano-quantum dots are uniformly dispersed.

[0071] 4. Ni metal salt Ni(NO 3 ) 2 Adsorption on MoC / C materials

[0072] First, weigh 300 mg of nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O) was dispersed in 20 mL of ethanol solution to prepare an ethanol solution with a Ni mass concentration of 3 mg / mL. Then 80 mg of MoC / C material was weighed and evenly dispersed in 120 mL of ethanol solution. 6 mL of ethanol solution with a Ni mass fraction of 3 mg / mL was added during magnetic stirring. After stirring at room temperature for 24 hours, the precipitate was collected by centrifugation and washed twice with ethanol. Finally, it was placed in a vacuum oven at 60°C for 4-12 hours to prepare Ni metal salt Ni(NO 3 ) 2 Adsorption on MoC / C composites.

[0073] 5. Preparation of Ni@MoC / C composites with high catalytic activity supported by Ni single atoms

[0074] The Ni metal salt Ni(NO 3 ) 2 The adsorbed MoC / C composite material was placed in a corundum boat, and then the corundum boat was placed in a tube furnace and heated to 800 °C at a rate of 5 °C / min under an argon atmosphere. After being kept at 800 °C for 1 hour, it was naturally cooled to room temperature with the furnace, and the black powder material obtained was collected, namely, the Ni single atom-loaded Ni@MoC / C composite material.

[0075] The XRD pattern of the Ni@MoC / C composite material with high catalytic activity supported by Ni single atoms prepared in this example is shown in FIG. Figure 1 As shown in the scanning electron microscope image Figure 2 As shown, the transmission electron microscope and surface scanning element distribution are as follows Figure 3 As shown in Figure 2, the nitrogen isothermal adsorption-desorption curve and pore size distribution are shown in Figure 2. Figure 4 As shown, the X-ray photoelectron spectrum is Figure 5 As shown, the X-ray absorption fine structure spectrum is Figure 6 As shown. Figure 1 It can be seen that the phase of the composite material is a composite material of carbon and MoC. Since Ni exists in the form of a single atom, there is no characteristic peak. Figure 2 It can be seen that the composite material is a uniform polyhedral structure with a particle size of about 200 nm. Figure 3 It can be seen that the composite material is a carbon composite material loaded with Ni single atoms and MoC ultrafine nano-quantum dots of about 2-3 nm in size, and the carbon material has a hollow structure and the elements are evenly distributed. Figure 4 It can be seen that the composite material has a large specific surface area (831.42 m 2 / g); from Figure 5 It can be seen that the composite material contains elements such as C, N, Mo, and Ni. Figure 3 Element distribution Figure 1 to; from Figure 6 It can be seen that Ni in the composite material exists in the form of single atoms. In addition, the inductively coupled plasma emission spectroscopy (ICP) test results show that the mass fraction of Ni in the composite material is 0.95% and the mass fraction of Mo is 9.84%.

[0076] In this embodiment, the Ni@MoC / C composite material is only used as a positive electrode sulfur-carrying material in the field of lithium-sulfur batteries.

[0077] Sublimated sulfur and Ni@MoC / C composite material were weighed in a mass ratio of 7:3, ground and mixed evenly, and then the mixed material was placed in a thin glass tube and evacuated until the vacuum degree in the glass tube reached below 10 mbar and maintained for 10 min. Then, the glass tube was melted and sealed with an acetylene torch. The glass tube was placed in an oven, heated to 155°C by molten sulfur filling, and kept warm for 12 hours. After cooling, the sulfur-carbon composite material was obtained.

[0078] The obtained sulfur-carbon composite positive electrode material, conductive agent (conductive carbon black, super P) and binder (polyvinylidene fluoride, PVDF) were mixed in a mass ratio of 8:1:1, and methyl pyrrolidone (NMP) was used as a solvent. The mixture was evenly mixed by ball milling to form a slurry. The ball milling speed was 150 r / min and the ball milling time was 2 hours. The slurry was then coated on the aluminum foil current collector with a scraper. The scraper blade height was 150 μm. The pole piece was placed in a vacuum oven and baked at 60°C for 6 hours. After drying, the lithium-sulfur battery positive pole piece was prepared. The coating surface density sulfur loading was about 1 mg / cm 2 .

[0079] The positive electrode sheet of the lithium-sulfur battery was cut into a disc with a diameter of 12 mm as the working electrode (positive electrode), the metal lithium sheet was used as the counter electrode (negative electrode), and the polypropylene separator (celgard 2400), containing 1 mol / L lithium bistrifluoromethanesulfonyl imide (LiTFSI) lithium salt, 1% lithium nitrate and 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME) (volume ratio of 1:1) solvent electrolyte, assembled into a 2025 button lithium-sulfur battery. The battery was tested for cycle performance, with the charge and discharge current of the first three cycles being 0.2 C, and then tested at different rates, where 1C=1675 mAh / g, and the test voltage range was 1.7~2.8V.

[0080] The Ni@MoC / C composite material is used as a sulfur-carrying material for the positive electrode of a lithium-sulfur battery. The cyclic voltammetry curve of the battery at a scan rate of 0.1 mV / s is shown in FIG. Figure 7 The corresponding redox peaks are shown in Fig. 9 As shown, the performance of different rates is as follows Fig.10 As shown, the cycling performance at 0.5 C current is Fig.11 The cycling performance at 1 C current is shown in Fig.12 shown.

[0081] Example 2

[0082] A Ni@MoC / C composite material containing single atom loading is prepared and used as a cathode sulfur-carrying material and a diaphragm modification material in lithium-sulfur batteries.

[0083] The steps of the preparation method of the Ni@MoC / C composite material containing single atom loading and the process of preparing the pole piece as a sulfur-loaded positive electrode carrier in this embodiment are completely consistent with those in Example 1. The steps of modifying the diaphragm with the Ni@MoC / C composite material as a modifying material are as follows:

[0084] The Ni@MoC / C composite material, conductive agent (conductive carbon black, super P) and binder (polyvinylidene fluoride, PVDF) were mixed in a mass ratio of 8:1:1, and methyl pyrrolidone (NMP) was used as solvent to prepare a slurry with a mass concentration of 1 mg / mL of Ni@MoC / C composite material. After ultrasonic treatment for 30 minutes, magnetic stirring was performed for 6 hours to mix evenly. Then, the material was evenly dispersed and covered on one side of the polypropylene diaphragm (celgard2400) by filtration. After vacuum drying, the Ni@MoC / C-PP modified diaphragm was prepared. The loading amount of Ni@MoC / C composite material on the diaphragm surface was about 0.1 mg / cm 2 Finally, the modified diaphragm was cut into discs with a diameter of 19 mm.

[0085] A 2025 button-type lithium-sulfur battery was assembled using a Ni@MoC / C composite sulfur-loaded electrode as the positive electrode, a Ni@MoC / C composite modified separator, a metal lithium negative electrode, and the same electrolyte as in Example 1. The electrochemical performance test method was the same as in Example 1.

[0086] The Ni@MoC / C composite material was used as both a positive electrode sulfur-carrying material and a diaphragm modification material in a lithium-sulfur battery. The cyclic voltammetry curve of the battery at a scan rate of 0.1 mV / s was as follows: Figure 7 The corresponding redox peaks are shown in Fig. 9 As shown, the performance of different rates is as follows Fig.10 As shown, the cycling performance at 0.5 C current is Fig.11 The cycling performance at 1 C current is shown in Fig.12 shown.

[0087] Comparative Example 1

[0088] Preparation of carbon materials containing only MoC and no single atomic Ni and performance testing of their application in lithium-sulfur batteries.

[0089] Different from Example 1, the preparation process of the carbon material containing only MoC in Comparative Example 1 is the first three steps of the preparation process of Example 1, and the carbon material MoC / C with uniformly dispersed MoC nano-quantum dots is obtained.

[0090] The MoC / C material is used as a sulfur-carrying material in the positive electrode of a lithium-sulfur battery. The sulfur-carrying process, preparation of the positive electrode sheet, assembly and testing of the lithium-sulfur battery are completely consistent with those in Example 1.

[0091] MoC / C materials are used as sulfur-bearing materials for the positive electrode of lithium-sulfur batteries. The cyclic voltammetry curve of the battery at a scan rate of 0.1 mV / s is shown in Figure 8 The corresponding redox peaks are shown in Fig. 9 As shown, the performance of different rates is as follows Fig.10 As shown, the cycling performance at 0.5 C current is Fig.11 The cycling performance at 1 C current is shown in Fig.12 shown.

[0092] Comparative Example 2

[0093] Preparation of carbon materials containing only single-atom Ni and no MoC and performance testing of their application in lithium-sulfur batteries.

[0094] The preparation method of the carbon material containing single-atom Ni and no MoC in this embodiment is as follows:

[0095] 1. Preparation of zinc-based metal organic framework material ZIF-8

[0096] First, 9 g of zinc nitrate (Zn(NO 3 ) 2 6H 2 O) was added to 450 mL of methanol (CH 3 OH) solution, and then 9.24 g of 2-methylimidazole (C 4 H 6 N 2 ) was added to another 450 mL of methanol solution. After the two solutions were completely dissolved, the 2-methylimidazole solution was added to the zinc nitrate solution, ultrasonicated for 10 minutes, and magnetically stirred at room temperature for 24 hours. The precipitate was collected by centrifugation at a speed of 6000 r / min and a centrifugal time of 2 min. Finally, it was washed with methanol solution for more than three times and dried in a vacuum oven at 60 ℃ for 6 hours to obtain ZIF-8 nanoparticles.

[0097] 2. Preparation of Carbon Material C

[0098] The ZIF-8 powder obtained in step 2 is placed in a corundum boat, and then the corundum boat is placed in a tubular furnace, and the temperature is increased to 910°C at a rate of 5°C / min under an argon atmosphere. After being kept at 910°C for 3 hours, it is naturally cooled to room temperature with the furnace. During the high-temperature carbonization process, the zinc in the ZIF-8 evaporates at high temperature along with the airflow, and the black powder material obtained is collected, namely, carbon material C.

[0099] 3. Ni metal salt Ni(NO 3 ) 2 Adsorbed on C material

[0100] First, weigh 300 mg of nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O) was dispersed in 20 mL of ethanol solution to prepare an ethanol solution with a Ni mass concentration of 3 mg / mL. Then 80 mg of C material was weighed and evenly dispersed in 120 mL of ethanol solution. 6 mL of ethanol solution with a Ni mass fraction of 3 mg / mL was added during magnetic stirring. After stirring at room temperature for 24 hours, the precipitate was collected by centrifugation and washed twice with ethanol. Finally, it was placed in a vacuum oven at 60°C for 4-12 hours to prepare Ni metal salt Ni(NO 3 ) 2 Adsorbed C material.

[0101] 4. Preparation of Ni@C Materials Loaded with Ni Single Atoms

[0102] The Ni metal salt Ni(NO 3 ) 2The adsorbed C material was placed in a corundum boat, which was then placed in a tubular furnace and heated to 800 °C at a rate of 5 °C / min under an argon atmosphere. After being kept at 800 °C for 1 hour, it was naturally cooled to room temperature with the furnace, and the black powder material obtained was collected, namely, the Ni single atom-loaded Ni@C material.

[0103] The Ni@C material is used as a sulfur-carrying material in the positive electrode of a lithium-sulfur battery. The sulfur-carrying process, preparation of the positive electrode sheet, assembly and testing of the lithium-sulfur battery are completely consistent with those in Example 1.

[0104] The Ni@C material is used as the sulfur-carrying material for the positive electrode of lithium-sulfur batteries. The cyclic voltammetry curve of the battery at a scan rate of 0.1 mV / s is as follows: Figure 8 The corresponding redox peaks are shown in Fig. 9 As shown, the performance of different rates is as follows Fig.10 As shown, the cycling performance at 0.5 C current is Fig.11 The cycling performance at 1 C current is shown in Fig.12 shown.

[0105] Comparative Example 3

[0106] Preparation of carbon materials free of single-atom Ni and MoC and performance testing of their application in lithium-sulfur batteries.

[0107] Different from Comparative Example 2, the preparation process of the carbon material in Comparative Example 3 is the first two steps of the preparation process in Comparative Example 2, and a nitrogen-doped carbon material is obtained.

[0108] The carbon material is used as the sulfur-carrying material in the positive electrode of the lithium-sulfur battery. The sulfur-carrying process, preparation of the positive electrode sheet, assembly and testing of the lithium-sulfur battery are completely consistent with those in Example 1.

[0109] The carbon material without single-atom Ni and MoC is used as the positive electrode sulfur-carrying material in the lithium-sulfur battery. The cyclic voltammetry curve of the battery at a scan rate of 0.1mV / s is as follows Figure 8 The corresponding redox peaks are shown in Fig. 9 As shown, the performance of different rates is as follows Fig.10 As shown, the cycling performance at 0.5 C current is Fig.11 The cycling performance at 1 C current is shown in Fig.12 shown.

[0110] from Figure 7 Cyclic voltammetry curves of the embodiments, Figure 8 Cyclic voltammetry curves of the comparative example and Fig. 9From the redox peak comparison diagram, it can be seen that the reduction peak peak positions of Example 1 are 2.293 V and 2.054 V, respectively, and the reduction peak peak positions of Example 2 are 2.301 V and 2.057 V, respectively, while the reduction peak peak positions of Comparative Example 1 are 2.281 V and 2.039 V, respectively, the reduction peak peak positions of Comparative Example 2 are 2.269 V and 2.028 V, respectively, and the reduction peak peak positions of Comparative Example 3 are 2.254 V and 2.019 V, respectively. The two reduction peak positions of the embodiments are significantly greater than those of the comparative examples; the oxidation peak peak positions of Example 1 and Example 2 are 2.33 V and 2.343 V, respectively, and the oxidation peak peak positions of Comparative Example 1, Comparative Example 2 and Comparative Example 3 are 2.381 V, 2.381 V and 2.413 V, respectively. V, the oxidation peaks of the embodiments are significantly smaller than those of the comparative examples, indicating that the oxidation or reduction reactions of the embodiments occur earlier than those of the comparative examples, indicating that the MoC composite material containing single-atom Ni and nano-quantum dots in the embodiments can significantly improve the reaction rate of polysulfide conversion and has an obvious synergistic catalytic effect.

[0111] like Fig. 9 The figure shows the rate discharge performance of the embodiments and comparative examples. The discharge gram capacities of embodiment 1 after the third cycle at 0.2 C, 0.5 C, 1 C and 2C rates are 1139.7 mAh / g, 919.9 mAh / g, 781.3 mAh / g and 661.7 mAh / g, respectively; the discharge gram capacities of embodiment 2 are 1449.5 mAh / g, 1162.4 mAh / g, 994 mAh / g and 819.4 mAh / g, respectively; the discharge gram capacities of comparative example 1 are 1145 mAh / g, 910.3 mAh / g, 760.3 mAh / g and 585.1 mAh / g, respectively; the discharge gram capacities of comparative example 2 are 935.6 mAh / g, 742.3 mAh / g, 616.7 mAh / g and 498.9 mAh / g, respectively; and the discharge gram capacities of comparative example 3 are 999.3 mAh / g, 1162.4 mAh / g, 994 mAh / g and 819.4 mAh / g, respectively. mAh / g, 673 mAh / g, 436.5 mAh / g and 258.7 mAh / g, it can be seen that the rate performance of the embodiment is significantly better than that of the comparative example.

[0112] like Fig.10The figure is the cycle performance diagram of the embodiment and the comparative example at 0.5 C rate. The first discharge gram capacity of embodiment 1 and embodiment 2 is 1384.1 mAh / g and 1675.8 mAh / g respectively, while the first discharge gram capacity of comparative example 1, comparative example 2, and comparative example 3 is 1247.2 mAh / g, 1242.3 mAh / g and 1192.5 mAh / g respectively; after 300 cycles, the discharge gram capacity of embodiment 1 and embodiment 2 is 570.3 mAh / g and 715.7 mAh / g respectively, while the discharge gram capacity of comparative example 1, comparative example 2, and comparative example 3 is 525.1 mAh / g, 501.3 mAh / g, 423.2 mAh / g respectively. The discharge capacity and cycle stability of the embodiment are higher than those of the comparative example. Fig.11 The figure is the cycle performance diagram of the embodiments and comparative examples at 1 C rate. The discharge capacities of Embodiment 1 and Embodiment 2 after 300 cycles are 554 mAh / g and 651.2 mAh / g, respectively. The discharge capacities of Comparative Example 1, Comparative Example 2 and Comparative Example 3 after 300 cycles are 516.6 mAh / g, 483.2 mAh / g and 419.5 mAh / g, respectively. The discharge capacity and cycle stability of the embodiments are significantly higher than those of the comparative examples.

[0113] Therefore, it can be seen from the experimental data that the Ni@MoC / C composite material containing Ni single atoms and MoC nano-quantum dots is prepared and used as a positive electrode sulfur-carrying material or a diaphragm modification material in a lithium-sulfur battery in terms of discharge capacity, cycle performance, rate performance, and reaction kinetics. The performance of the embodiment is significantly better than that of the comparative example, showing better electrochemical performance. Therefore, the application of the Ni@MoC / C composite material containing Ni single atoms and MoC nano-quantum dots as a sulfur-carrying material or a modified diaphragm material in a lithium-sulfur battery proposed by the present invention is feasible, and the performance improvement effect is significant.

[0114] The present invention provides a method for preparing a Ni@MoC / C composite material loaded with Ni single atoms and MoC nano-quantum dots with high catalytic activity. The single atoms and MoC nano-quantum dots are evenly dispersed, have high electrical conductivity and high catalytic activity, and exhibit relatively excellent electrochemical performance when applied in lithium-sulfur batteries. This provides a new method and new idea for solving the problems of low specific capacity, poor high-rate performance, poor cycle performance, shuttle effect, volume expansion, etc. of lithium-sulfur batteries. In addition, the preparation method has mild reaction conditions, simple process, environmental friendliness, easy batch preparation, and good application prospects.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material with high catalytic activity, characterized in that: The following steps are involved: (1) Preparation of zinc-based metal organic framework material Zn-MOF; (2) Evenly dispersing the molybdenum source on the zinc-based metal organic framework material Zn-MOF; (3) carbonizing the material obtained in step (2) at high temperature under an inert gas atmosphere to obtain a carbon material MoC / C in which MoC nano-quantum dots are uniformly dispersed; (4) Adsorbing metal X salt onto MoC / C material by solution impregnation method; (5) carbonizing the material obtained in step (4) at high temperature under an inert gas atmosphere to obtain a single-atom-loaded X@MoC / C composite material with high catalytic activity; The molybdenum source in step (2) is molybdenum hexacarbonyl (Mo(CO)6), and the mass ratio of molybdenum hexacarbonyl to Zn-MOF is 2:100 to 50:100; The inert gas in step (3) is nitrogen or argon, the high temperature carbonization temperature is 900-1100°C, and the time is 1-4 hours; In step (4), the solution impregnation method is to disperse the MoC / C material in a X metal salt solution, impregnate it under magnetic stirring for 6 to 18 hours, collect the precipitate by centrifugation or suction filtration, wash it with ethanol, and dry it in a vacuum oven at 60° C. for 4 to 12 hours; wherein the metal element X in the X metal salt solution is one or more transition metal elements, including nickel, cobalt, iron, manganese, and chromium, and the X metal salt includes acetate, nitrate, chlorate, and chloride of the X metal, and the concentration of the metal ion in the X metal salt solution is 0.1 to 10 mg / mL; The inert gas in step (5) is nitrogen or argon, the high temperature carbonization temperature is 500-800°C, and the time is 1-2 hours; In the single-atom-loaded X@MoC / C composite material with high catalytic activity, carbon is used as a carrier material and has a rich pore structure, and the mass fraction of carbon is 50% to 99%; MoC is distributed on the carbon carrier in the form of nano-quantum dots, and the average size of MoC is less than 5 nm, and the mass fraction is 1% to 50%; the metal element X exists in the form of a single atom, and the mass fraction ranges from 0.1% to 2%.

2. A lithium-sulfur battery, characterized in that: The positive electrode or the separator of the lithium-sulfur battery contains the single-atom-loaded X@MoC / C composite material with high catalytic activity prepared by the preparation method according to claim 1.

3. The use of the single-atom-supported X@MoC / C composite material with high catalytic activity according to claim 2 in a lithium-sulfur battery, characterized in that: The X@MoC / C composite material is used as a cathode sulfur-carrying material or a modified commercial battery separator, or as both a cathode sulfur-carrying material and a modified commercial battery separator.

4. The use according to claim 3, characterized in that: The X@MoC / C composite material is used as the positive electrode sulfur-carrying material. The specific steps are as follows: 1) After the sublimated sulfur and the X@MoC / C composite material are uniformly mixed in a certain proportion, the sulfur powder and the composite material are mixed by melting sulfur in a vacuum or inert gas protection atmosphere to obtain a sulfur / carbon composite cathode material, and the heating temperature is kept at 155 °C for 12 to 24 hours, wherein the mass proportion of the X@MoC / C composite material in the sulfur / carbon composite cathode material is 5% to 50%; 2) The sulfur / carbon composite positive electrode material, conductive agent and binder obtained in step 1) are mixed in a certain proportion, and nitrogen methyl pyrrolidone is used as a solvent. The mixture is evenly mixed to form a slurry, and then the slurry is coated on the current collector. After vacuum drying, a positive electrode sheet of a lithium-sulfur battery is prepared; 3) Assemble the lithium-sulfur battery positive electrode sheet and lithium negative electrode, separator, electrolyte and shell obtained in step 2) to obtain a lithium-sulfur battery.

5. The use according to claim 3, characterized in that: The X@MoC / C composite material is used as a modified commercial battery separator. The specific steps are as follows: (1) Mixing the X@MoC / C composite material with a conductive agent and a binder in a certain proportion, using nitrogen methyl pyrrolidone as a solvent, mixing them evenly to form a slurry, and then applying it on one side of a commercial diaphragm by scraping, filtering or spraying, and vacuum drying (2) to obtain a modified diaphragm, wherein the commercial diaphragm is a microporous polyolefin diaphragm, a ceramic diaphragm or a non-woven fabric diaphragm; The modified diaphragm obtained in step (1) is assembled with the positive electrode, the negative electrode, the electrolyte and the shell to obtain a lithium-sulfur battery.